Therapeutic Alliance and Group Cohesion in Group Therapy based on Mentalization and Dialectical Behavior in Borderline Personality Disorder: A randomized controlled clinical trial - Leila Khabir; Nourollah Mohamadi; Changiz Rahimi; Seyed Ali Dastgheib (Shiraz University of Medical Sciences, 2018)
Background: Effective common factors such as therapeutic alliance and group cohesion play essential roles in outcome treatment in borderline personality disorder. The present study aimed to investigate the role of therapeutic alliance and group cohesion in group therapy based on mentalization and dialectical behavior in borderline personality disorder. Methods: This is a single-blind randomized controlled clinical trial conducted on 36 patients diagnosed with BPD (12 in each three groups). They were examined by a semi-structured clinical interview. Data were collected from March 2017 to June 2017. All screening and performance procedures were performed daily in Hefez hospital, Shiraz. Patients were selected through targeted sampling. Data were entered into SPSS, version 21, by using repeated measures and simple regression analysis and analyzed by one who was blind to the groups. The computer method was used for randomization. The participants were categorized into intervention and control groups. Before, immediately and two months after the intervention, the participants filled out the Borderline Personality Disorder Severity Index (BPDSI), Working Alliance Inventory (WAI), Group Cohesion Scale (GCS), Beck Anxiety Inventory (BAI), and Beck Depression Inventory-II (BDI-II) questionnaires. Results: After the intervention, therapeutic alliance (p=0.005) and group cohesion (p=0.0001) in both experimental groups had significantly higher scores compared to the control group. Conclusion: The two relationship elements were found to contribute to psychotherapy outcome. Therapeutic alliance and group cohesion had also been estimated to account for at least as much variance in psychotherapy outcome as specific therapeutic interventions.